AB0412 Dynamics of quantitative body composition indices by the method of dual-energy x-ray absorptiometry (DRA) in patients with early ra depending on the achieved activity of the disease. (12th June 2018) - Gorbunova, Y.; Popkova, T.; Kondratyeva, L.; Smirnov, A.; Nasonov, E.
Abstract : Background: Adipose tissue an active endocrine organ. In pts with RA the redistribution of body fat mass. Using BMI and WC do not allow to distinguish between fat and lean (muscle) mass. Performing dual-energy X-ray absorptiometry allows to specify the quantitative composition of the body(mass of adipose tissue and muscle) in pts with early RA. Objectives: to compare the indicators of the quantitative composition of the body in groups of RApts with different disease activity before and after the appointment of therapy. Methods: included 37pts with early RA(ACR/EULAR2010), 57 [46.5, 62] yrs, duration of disease 6 [5.5, 15.5]mths, IgMRF seropositive antiCCP, with high RA activity(DAS285.5 [5.1, 6], SDAI 32.4 [22.4, 42], CDAI 29 [19.7, 39.5]). After inclusion in the study, all pts started receiving MTX 10 [10–15 mg/week), after 12 weeks, with ineffective MTX, ADA 40 mg/ 2 weeks was prescribed. The quantitative composition of the body was determined initially and after 6mths by means of DXA using the apparatus HOLOGIC, analysing the following parameters:the total, of fat and lean mass. Results: By the 24th week of therapy, 13 (35%)pts with earlyRA received combined therapy(ADA, MTX), 24 (65%) pts with RA monotherapy MTX. Depending on the activity of RA(DAS28)by the 24th week of therapy, pts are divided into 2groups: I(n=18) pts with remission/low activity, II(n=19)with moderate/high RA activity (table 1). Initially, the groups differed in fat mass:this index was higher in the group of pts with moderate/high activity persisting, compared with the group of pts with remission/low activity of RA:30.2 kg versus 19.4 kg. In the I group of pts before the treatment and after 6mths of therapy, a statistically significant decrease in muscle mass was observed:from 45.2 kg to 41.6 kg. A decrease in the mass of adipose tissue after 24 weeks of therapy was noted in the IIgroup of pts with RA:from 30.2 kg to 28.2 kg. The difference in the indices between the groups by the 6 month of therapy was noted for the mass of adipose tissue. This composition of the body score was also higher in pts with moderate and high RA activity, compared to the group of pts with remission/low RA activity: 28.2 kg versus 18.9 kg(p<0.05 in all cases). Conclusions: pts with RA who achieved Igroup after 6 mths of therapy initially had a smaller volume of adipose tissue, compared with pts with moderate and high RA activity. Despite the achievement of remission after 6mths of therapy, a loss of lean mass(probably the development of rheumatoid cachexia) continued in some pts, but these data need confirmation in studies with a large number of pts and a longer period of follow-up. Disclosure of Interest: None declared